Colloquial Spanish as a Pedagogical Strategy: Features and Relation with The Discursive Genre in The University Classroom - García Cardona, Juan (2020)
The university class shows a communicative situation that has been characterized, sometimes, as a high formality discourse. In relation to the situation that is established in the classroom, the teacher will choose an appropriate language. With this research, we intend to analyze the characteristics of the linguistic strategy of several professors of the University of Malaga, by identifying typical features of colloquial Spanish, with the intention of determining whether these features predominate in the language used by teachers. Colloquiality has been defined as an informal register of the conversation itself, so the presence of these colloquial features in the classroom will allow us to approach the communicative situation in which a university class develops. The sample consists of seven professors of which 20 variables characteristic of colloquial Spanish have been measured qualitatively. Ordered from least to greatest, the study subjects have presented 10, 13, 14, 15, 18, 18 and 19 of all the proposed features, suggesting a predominance of colloquiality in the university class.